2016
DOI: 10.1158/1078-0432.ccr-15-2461
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase (LOX) Transcriptionally Regulates SNAI2 Expression and TIMP4 Secretion in Human Cancers

Abstract: Purpose: Epithelial-to-mesenchymal transition (EMT) is important in cancer progression and metastasis. We and others have previously reported that lysyl oxidase (LOX) is overexpressed in aggressive cancers, is associated with increased mortality, and regulates EMT. However, the mechanism by which LOX mediates EMT is unknown. In this study, we investigated the effect of LOX on mediators of EMT.Experimental Design: We used chromatin immunoprecipitation and promoter luciferase assays to determine the target gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
(48 reference statements)
1
43
0
Order By: Relevance
“…It has been reported that LOX is associated with tumor malignancy, especially with distant metastasis that includes bone metastasis, in several types of cancers such as thyroid, breast, nasopharyngeal, gastric and pancreatic cancers. 23,24,27,[34][35][36][37] With reference to HCC, some reports have shown an association between LOX and angiogenesis markers such as vascular endothelial growth factor (VEGF), but none has revealed an association with EMT or metastasis in HCC. We exhaustively examined the role of LOX in HCC using a large transcriptome matrix, which showed that high LOX expression is closely associated with EMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that LOX is associated with tumor malignancy, especially with distant metastasis that includes bone metastasis, in several types of cancers such as thyroid, breast, nasopharyngeal, gastric and pancreatic cancers. 23,24,27,[34][35][36][37] With reference to HCC, some reports have shown an association between LOX and angiogenesis markers such as vascular endothelial growth factor (VEGF), but none has revealed an association with EMT or metastasis in HCC. We exhaustively examined the role of LOX in HCC using a large transcriptome matrix, which showed that high LOX expression is closely associated with EMT.…”
Section: Discussionmentioning
confidence: 99%
“…LOX is a copper‐dependent amine oxidase that catalyzes the final enzymatic step required for cross‐linking of collagen and elastin molecules in the extracellular matrix . In malignant tumors, LOX is involved in the remodeling of cancer stroma, and affects cancer metastasis or accelerates dedifferentiation of cancer cells . High LOX expression is reportedly associated with cancer malignancy and cancer metastasis, and reflects patient prognosis in several types of cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Stromal-derived LOX could create a milieu that is suitable for metastastic cancer cells. 34,46 Recently, LOX has been considered as one target to control the metastasis of prostate cancer.…”
mentioning
confidence: 99%
“…25 RET mutations upregulate the biogenesis of miRNAs, 26 and emerging work has identified miR30a as important in maintaining PTC differentiation through the inhibition of lysyl oxidase. 27,28 In addition, pAKT localization has been shown to be dependent on the presence of RET rearrangement. 29 In non-invasive areas of PTC co-expressing RET, pAKT expression was diffuse and cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%